2021
DOI: 10.1039/d1sc00133g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of quaternary centres by single electron reduction and alkylation of alkylsulfones

Abstract: A new method for the generation of tertiary radicals thorugh single electron reduction of alkylsulfones promoted by Zn and 1,9-phenanthlorine has been developed. These radicals could be employed in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“… 3 The photogeneration of these radicals has been only sparsely reported using Barton esters, 32 N -(acyloxy)phthalimides, 33 alkyl N -phthalimidoyl oxalates, 34 and alkyl carboxylates. 5b Thermal generation of these intermediates involved electrophiles such as alkyl halides 35 or alkylsulfones, 36 despite that in some cases, the desired C(sp 3 )–C(sp 3 ) bond formation failed to occur. 37 …”
Section: Resultsmentioning
confidence: 99%
“… 3 The photogeneration of these radicals has been only sparsely reported using Barton esters, 32 N -(acyloxy)phthalimides, 33 alkyl N -phthalimidoyl oxalates, 34 and alkyl carboxylates. 5b Thermal generation of these intermediates involved electrophiles such as alkyl halides 35 or alkylsulfones, 36 despite that in some cases, the desired C(sp 3 )–C(sp 3 ) bond formation failed to occur. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Building on Baran’s report, Nambo and Crudden reported an approach for the generation of reactive tertiary radicals through single-electron reduction of alkylsulfones 87 - 1 promoted by Zn and 1,10-phenanthroline (Scheme A) . The formed intermediates underwent Giese reaction with electron-withdrawing alkenes to form new quaternary carbon centers upon radical addition and hydrogenation.…”
Section: Radical-mediated Desulfonylation Of Sulfones Via C–s Bond Cl...mentioning
confidence: 99%
“…As expected, the formation of ring-opening product 86-3k from cyclopropylmethyl sulfone, 5-exo-trig cyclized product 86-3l from linear alkenyl sulfone, and racemic product from an enantioenriched sulfone 86-3m was observed, suggesting that a single-electron radical cross-coupling pathway Building on Baran's report, Nambo and Crudden reported an approach for the generation of reactive tertiary radicals through single-electron reduction of alkylsulfones 87-1 promoted by Zn and 1,10-phenanthroline (Scheme 87A). 304 The formed intermediates underwent Giese reaction 305 the present method was demonstrated through intramolecular cyclization of sulfones possessing olefin moieties to give a variety of spiro structures (Scheme 87B). Desulfonylative borylation of benzyl sulfones 88-1 with bis(pinacolato) diboron (B 2 pin 2 ) was revealed by Crudden, Nambo, and co-workers in 2019 (Scheme 88A).…”
Section: Radical-mediated Desulfonylation Of (Fluoro)alkylmentioning
confidence: 99%
“…7 Very recently, Crudden and her group members were able to generate quaternary centers by reducing alkylsulfones using Zn and 1,10-phenanthroline to generate tertiary radicals. 8 Recent developments in photoredox chemistry have enabled Hu 9 a and others 9 b – d to develop strategies involving radical fluoroalkylation. And the Gouverneur and Davis group used a photocatalytic radical modification of proteins.…”
mentioning
confidence: 99%
“…Inspection of the literature also provided evidence for this type of fragmentation. 8 Note, however, that generation of an alkyl sulfonyl radical cannot be ruled out. In fact, Wu et al and Ley et al reported the addition of alkyl sulfonyl radical to electron-deficient olefins.…”
mentioning
confidence: 99%